Pengaruh Pemahaman Perpajakan Tentang Tarif Pajak, Sanksi Pajak dan Keadilan Pajak Terhadap Persepsi Mahasiswa Akuntansi Mengenai Penggelapan Pajak Di Masa Pasca Pandemi Covid 19 - Belinda Putri Astiawan; Andi Kartika (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2022)
As a result of these government policies impacted on various sectors, especially in the industrial and trade sectors. In this sector many parties experience losses. Where companies do not get income from the sale of their merchandise as a result of government policies regarding restrictions on community activities. As a result, companies experience losses and are unable to pay their taxes. During these periods the government provided a policy of tolerating corporate tax payments. The purpose of this study is to determine the influence of tax understanding of tax rates, tax sanctions, and tax fairness on accounting students' perceptions of tax evasion in the post-Covid 19 pandemic. this is all population or all accounting students. The findings in this research are the understanding of tax justice that influences the perceptions of accounting students regarding tax evasion in the post-covid 19 pandemic. tax evasion in the post-covid-19 pandemic.